CHANGES IN CAROTID LOCAL STIFFNESS DURING A SIX-YEARS FOLLOW UP IN A GENERAL POPULATION: THE VOBARNO STUDY. (April 2021) - Paini, Anna; Aggiusti, Carlo; Stassaldi, Debora; Bertacchini, Fabio; Capellini, Sara; Arnoldi, Chiara; Salvetti, Massimo; Muiesan, Maria Lorenza
Abstract : Objective: Local carotid stiffness (Carotid PWV) is an independent predictor of cardiovascular events but few data are available on the progression of Carotid stiffness over time. The aim of the present longitudinal study was to analyze the progression of local carotid stiffness over a 6-year period in a general population in Northern Italy (Vobarno Study). Design and method: 123 subjects, age 55 ± 4 years (42% males, hypertension in 43% at baseline visit), underwent a baseline (BL) and a follow up (FU) visit, 6.2 ± 0.5 years apart. In all subjects laboratory examinations, measurements of blood pressure (BP) and of Carotid PWV (using an echotracking approach) were performed at BL and at FU. Progression rate of Carotid PWV (δCarotid_PWV/Year) was defined as (Carotid PWV at FU-Carotid PWV at BL)/years of FU. Results: In the overall population, Carotid PWV increased from 6.39 ± 1.41 at BL to 6.79 ± 1.18 m/s at FU (p < 0.05). δCarotid_PWV/Year was inversely related to BP (mean BP: r = -0.193, p < 0.05; pulse pressure: r = -0.1.81, p < 0.05) and to Carotid PWV at BL (r = -0.669, p < 0.001). No other correlation was observed between δCarotid_PWV/Year and demographic or laboratory parameters at BL. δCarotid_PWV/Year was also related to changes over time in BP values (δSystolicBP: r = 0.291, p < 0.01; δDiastolicBP: r = 0.266, p < 0.01; δMeanBP: r = 0.310, p < 0.0001). At multivariate analysis the variables independently related to the annual progression rate of Carotid PWV were Carotid PWV and mean BP at BL (beta -0.68, p < 0.0001, and beta 0.20, p < 0.05, respectively) and changes in mean BP during follow-up (beta 0.18, p < 0.05). Conclusions: In a general population sample in Northern Italy the main determinants of the increase in local carotid stiffness during a 6 years FU were local carotid stiffness and mean BP at BL and change in mean BP over time.